THE PHENOMENON OF MONEY POLITICS PRACTICES IN THE DIRECT ELECTION OF VILLAGE HEADS IN SUMBEREJEO VILLAGE, BONANG SUB-DISTRICT, DEMAK DISTRICT IN 2023 - Sarifudin, Muhammad; Faozi, Safik (fakultas hukum universitas PGRI Semarang, 2024)
The formulation of the problem in this study is